A psicanálise freudiana e o atual contexto científico da biologia da mente: uma discussão a partir das concepções sobre o ego - Bocchi, Josiane Cristina (Universidade Federal de São Carlos, 2010)
There were substantial changes in the 90s decade in brain researchs, when one begins to discuss the benefits of an alignment of interests between the areas of Neuroscience, Psychiatry, Cognitive Psychology and Psychoanalysis. Fact that it was linked to the change of perspective in sciences cognition and neuroscience, from a cognitive perspective to a dynamic and motivational view, in theory, more able to include aspects of subjectivity in the modern field of the study of mind. The psychoanalytic literature is very resistant to a renewed discussion of metapsychology, however there is no denying the construction of a notion of interdisciplinarity between the brain sciences and psychoanalysis (and psychological sciences in general). This Thesis intends to discuss some contemporary proposals of convergence between the neuropsychiatric and psychosocial formulations, in view of an interface between cognitive neuroscience and psychoanalysis, using Freudian concepts about the ego (Ich) as head theme. The search for the greatest integration between these formulations of the ego in Freudian theory could possibly contribute in reflecting on the debate on the rapprochement between psychoanalysis and neuroscience. We present the dialogue that some programs offer neuroscience for psychoanalysis. Does Freud's 19th century has to offer some contribution to what is named today as a new biology of mind? How to recover his thought could supply some conceptual and methodological shortcomings of these programs neurobiological? Psychoanalysis would be on the verge of losing its identity amid the current intellectual scene of the brain sciences? The aspirations of this multidisciplinary research about the mind and brain could open new horizons for psychoanalysis? The search of neuropsychological origins of Freudian metapsychology has opened a range of discussions, both in the neuroscience community, as in psychoanalysis. Instead of taking immediate support or a refusal to this interface is proposed that much like integration , this work suggests that the inquiries are referred to their own conceptual and methodological frame of neuroscience programs and examination of the Freudian theories, for knowing whether these concepts are open to this kind of reading - thus avoiding hasty conclusions and simplifications to that proposal.
Keywords: Psicanálise freudiana; Metapsicologia; Ego (Psicologia); Neurociência; Psychoanalysis freudian; Metapsychology; Ego; Neurosciences; CIENCIAS HUMANAS::FILOSOFIA